Determination of the dynamics of extraction of bas from the «Opornophyt» collection and its pharmacological activity - Oproshanska, Tetyana; Khvorost , Olha; Kukhtenko , Oleksandr; Voloshchuk , Natalia; Skrebtsova , Kateryna (Annals of Mechnikov's Institute, 2025)
We paid attention to phytomedicines which are used in the complex therapy of inflammatory processes of the musculoskeletal system, because these diseases take the 3rd place in the world as a most common and the second as a factor in permanent disability [1] and are accompanied by severe pain. The aim is to establish the dynamics of the extraction of polyphenols and hydroxycinnamic acids from the original plant collection «Opornofit» by the filtration extraction method and to study some aspects of its pharmacological activity. Materials and methods. The plant collection «Opornofit» was used to study. The plant raw materials for which were harvested in the Kharkiv and Vinnytsia regions. The extraction of the plant collection «Opornofit» was carried out by filtration extraction in a laboratory extractor to a total ratio of plant raw material:extract (DER) of 1:5. The dry residue and the quantitative content of total polyphenols and total hydroxycinnamic acids were determined in the obtained samples [17]. Extraction was carried out with 50% ethanol at room temperature. To study the analgesic and antiexudative activity of the liquid extract «Opornofit» 28 male Wistar rats were used, which were randomly divided into 4 groups of 7 animals. The study of the liquid extract at a dose of 100 mg/ml was carried out on the adjuvant arthritis (AA) model, which is an experimental model of rheumatoid arthritis in humans and is caused by the administration of Freund's complete adjuvant. The comparison solution was diclofenac sodium at a dose of 8 mg/ml [18]. Results and discussion. It was obtained 10 drains of 50 ml from the plant collection «Opornofit» by the method of filtration extraction. In each drain, the dry residue and the quantitative content of total polyphenols and total hydroxycinnamic acids were determined. Given the amount of dry residue, the content of total polyphenols and total hydroxycinnamic acids, effective and rational extraction occurs up to drain 5 inclusive. The liquid extract «Opornofit» in the model of adjuvant arthritis showed significantly higher analgesic activity on the 14th and 21st day of use than the reference drug diclofenac sodium. At the same time, its antiexudative activity was slightly inferior to diclofenac sodium on the 14th day of use and was higher on the 21st. Thus, it can be noted that the analgesic and antiexudative activity of the liquid extract «Opornofit» reaches its maximum peak in the second and third weeks of treatment, which corresponds to the acute and peak phase of inflammation. At the same time, the reference drug diclofenac sodium is not recommended for use for such a long period due to the development of severe adverse reactions, which are absent with prolonged use of the liquid extract. Conclusions. For the first time, the dynamics of the extraction of total polyphenols and total hydroxycinnamic acids from the original plant collection «Opornofit» was studied using the filtration extraction method. For the first time, the previously predicted analgesic and anti-inflammatory activity was confirmed for a liquid extract based on the collection «Opornofit». It was found that in the model of adjuvant arthritis, the liquid extract exhibits higher analgesic activity on the 14th and 21st day of use and anti-exudative activity on the 21st day than the reference drug diclofenac sodium. These studies became another step in the process of introducing the new original plant collection «Opornofit» and a number of phytomedicines based on it into the modern practice of the domestic healthcare system. Keywords: filtration extraction method, liquid extract, analgesic activity, anti-exudative activity